2016
DOI: 10.1097/mao.0000000000001170
|View full text |Cite
|
Sign up to set email alerts
|

The Use of an Ultrasonic Serrated Knife in Transcanal Excision of Exostoses

Abstract: Objective To describe a novel approach for excision of exostoses and evaluate the outcomes of transcanal excision of exostoses using ultrasonic serrated knife-assistance vs. micro-osteotomes only. Study Design Retrospective analysis Setting Academic Tertiary Care Center Patients/Interventions Patients receiving a transcanal excision of exostoses between 2007 and 2016. Main outcome measures The outcomes and post-operative complications of 138 patients who received transcanal micro-osteotome only techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Haidar et al found favorable healing rates when utilizing a piezoelectric cutting device; however, they did not report rates of otorrhea findings nor the incidence of subjective pain at 3 weeks postoperation. They also noted 1 incidence of thermal injury out of 11 ears, which may have implications for our current findings 7 . Conversely, the OP group was the soonest on average to return to the water, but not significantly compared to OA, suggesting that most patients were subjectively and objectively well enough to return to previous activities (Table 4).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Haidar et al found favorable healing rates when utilizing a piezoelectric cutting device; however, they did not report rates of otorrhea findings nor the incidence of subjective pain at 3 weeks postoperation. They also noted 1 incidence of thermal injury out of 11 ears, which may have implications for our current findings 7 . Conversely, the OP group was the soonest on average to return to the water, but not significantly compared to OA, suggesting that most patients were subjectively and objectively well enough to return to previous activities (Table 4).…”
Section: Discussionmentioning
confidence: 53%
“…4 Furthermore, the piezoelectric knife has been suggested to emit vibrations that are outside the range of frequencies that would have negative implications on the cochlea; however, the referenced study only contained eleven total ears operated upon by the piezoelectric. 7 In a similar study by Salami et al, no inner ear issues were found after the removal of symptomatic external ear canal osteomas with a piezoelectric device, but this study also only had 10 subjects. 8 Similarly to the previous studies, it is important to note the substantially fewer number of ears operated on in the OP group when evaluating these current findings.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…7 In a series of 10 exostoses, Haidar et al did not find any complication. 6 This surgical technique would be interesting to evaluate over a larger series with long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%